The Binding Force of Goods/Services Procurement Contracts from the Perspective of Article 1338 of the Indonesian Civil Code - Andhika Ariayuda; Sarwono Hardjomuldjadi; Sami'an Sami'an; Dwi Edi Wibowo (Interdisciplinary Social Studies, 2025)
This article provides a comprehensive analysis of the binding force of procurement contracts within the framework of Article 1338 of the Indonesian Civil Code (KUH Perdata), which establishes that any legally executed agreement shall bind the parties with the force of law (pacta sunt servanda). Using a literature-based methodology, this study examines national regulations (the Indonesian Civil Code, public procurement legislation, Presidential Regulation No. 16/2018 and its amendments), legal doctrines of contract law and administrative law, as well as relevant judicial decisions. The findings show that procurement contracts possess a dual legal nature: they are private agreements governed by civil law while simultaneously being influenced by public law due to the state’s involvement and the use of public financial resources. As a result, their binding force is determined not only by compliance with the legal conditions for contract validity (Article 1320 of the Civil Code) but also by adherence to principles of transparency, accountability, efficiency, and regulatory conformity in public procurement. The study reveals that the application of Article 1338 to procurement contracts must consider: (1) the limits of freedom of contract, (2) standardized government procurement documents, (3) safeguards against abuse of power, and (4) dispute-resolution mechanisms such as objections, mediation, arbitration, or litigation. This article concludes that the binding nature of procurement contracts is not absolute; rather, it is contextual and conditioned by principles of good governance and public financial accountability. The study contributes to the development of procurement contract doctrine within the Indonesian legal system.